2′‐fucosyllactose: an abundant, genetically determined soluble glycan present in human milk. (18th November 2013) - Castanys‐Muñoz, Esther; Martin, Maria J; Prieto, Pedro Antonio
<x xml:space="preserve">Abstract</x> Lactose is the preeminent soluble glycan in milk and a significant source of energy for most newborn mammals. Elongation of lactose with additional monosaccharides gives rise to a varied repertoire of free soluble glycans such as 2′‐fucosyllactose (2′‐FL), which is the most abundant oligosaccharide in human milk. In infants, 2′‐FL is resistant to digestion and reaches the colon where it is partially fermented, behaving as soluble prebiotic fiber. Evidence also suggests that portions of small soluble milk glycans, including 2′‐FL, are absorbed, thus raising the possibility of systemic biological effects. 2′‐FL bears an epitope of the Secretor histo‐blood group system; approximately 70–80% of all milk samples contain 2′‐FL, since its synthesis depends on a fucosyltransferase that is not uniformly expressed. The fact that some infants are not exposed to 2′‐FL has helped researchers to retrospectively probe for biological activities of this glycan. This review summarizes the attributes of 2′‐FL in terms of its occurrence in mammalian phylogeny, its postulated biological activities, and its variability in human milk.